Description of two new species of the Genus Ducetia Stål 1874 (Orthoptera: Tettigoniidae: Phaneropterinae) from India - Tiwari, Chandranshu; Diwakar, Swati (Zootaxa, 2023)
In the present paper the genus Ducetia Stål 1874 in India is reviewed. The diagnostic characters for two new species of Ducetia Stål 1874, D. assamica sp. nov. from North-East India and D. rohinii sp. nov. from Western Ghats are described. The two species are part of Ducetia japonica species complex. Further information on the distribution and ecology of species is given. A key to studied species of Ducetia is presented. While morphologically similar, D. assamica and D. rohinii show distinct differences in their call structures. Our work demonstrates the importance of acoustic signals in taxonomic studies.